PENINGKATAN HASIL BELAJAR TEMATIK TERPADU DENGAN COOPERATIVE LEARNING TIPE STUDENT TEAM ACHIEVEMENT DIVISION DI SEKOLAH DASAR - Putra, Abdio; Fitria, Yanti (Universitas Negeri Padang, 2022)
This study aims of study to illustrate an increase in student scores in integrated thematic learning used the STAD cooperative model in class 4 elementary schools. This type of research is Classroom Action Research (PTK) used quantitative and qualitative approaches. The place of the research was carried out by the State Elementary School 27 Rawang, Pesisir Selatan Regency. The results of this study indicate: the assessment of the Learning Implementation Plan in cycle I 87.46% then increased in cycle II 97.22%, assessment of aspects of teachers and aspects of students in the first cycle was 82% then increased in the second cycle 96%, the assessment of attitudes in the first cycle was good, then in the second cycle it became very good, the assessment of the knowledge aspects for the first cycle obtained a value of 84.5 then increased in cycle II to a value of 89.5 , the assessment of the skills aspect in cycle I obtained a value of 75.3 then increased in cycle II to 93.